The language of the New Testament : context, history, and development - Porter, Stanley E., 1956-; Pitts, Andrew W. (Linguistic Biblical Studies, 2013)
In The Language of the New Testament , Stanley E. Porter and Andrew W. Pitts assemble an international team of scholars whose work has focused on the Greek language of the earliest Christians. Each essay moves forward the current understanding of the context, history or development of the language of the New Testament. The first section of the volume focuses on the social contexts and registers that provide the environment for language use and selection. The second section deals with issues surrounding the history of the Greek language and how its development has impacted the Greek found within the New Testament.